2017
DOI: 10.1111/sdi.12633
|View full text |Cite
|
Sign up to set email alerts
|

Impact of drugs on intradialytic hypotension: Antihypertensives and vasoconstrictors

Abstract: Intradialytic hypotension (IDH) is a common complication of hemodialysis and is associated with numerous adverse outcomes including cardiovascular events, inadequate dialysis, loss of vascular access, and death. It is estimated that approximately 20%–30% of all dialysis sessions are affected by IDH. In seeking ways to reduce the occurrence of IDH, dialysis providers often turn to pharmacological approaches: withholding antihypertensive medications prior to hemodialysis or administering vasoconstrictor medicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 47 publications
(44 reference statements)
0
32
0
Order By: Relevance
“…Nonmedication strategies for treating intradialytic hypotension, such as cardiovascular status optimization, UF rate minimization, and target-weight reassessment, should be prioritized. Medication options include midodrine, 71 arginine-vasopressin, [72][73][74][75][76] sertraline, 77,78 droxidopa, amezinium metilsulfate, 79 fludrocortisone, and carnitine. 71 In general, the evidence base for these strategies is relatively weak, with most studies being small and of short duration.…”
Section: Intradialytic Hypertension Nonementioning
confidence: 99%
See 1 more Smart Citation
“…Nonmedication strategies for treating intradialytic hypotension, such as cardiovascular status optimization, UF rate minimization, and target-weight reassessment, should be prioritized. Medication options include midodrine, 71 arginine-vasopressin, [72][73][74][75][76] sertraline, 77,78 droxidopa, amezinium metilsulfate, 79 fludrocortisone, and carnitine. 71 In general, the evidence base for these strategies is relatively weak, with most studies being small and of short duration.…”
Section: Intradialytic Hypertension Nonementioning
confidence: 99%
“…Medication options include midodrine, 71 arginine-vasopressin, [72][73][74][75][76] sertraline, 77,78 droxidopa, amezinium metilsulfate, 79 fludrocortisone, and carnitine. 71 In general, the evidence base for these strategies is relatively weak, with most studies being small and of short duration. 71 The most widely used is midodrine, an oral vasoconstrictor, although efficacy data are limited, 65 as is its availability outside the US (Table 3).…”
Section: Intradialytic Hypertension Nonementioning
confidence: 99%
“…On the one hand, medications that result in negative inotropy and chronotropy may lead to more IDH; on the other hand, slowing of heart rate and improved ventricular compliance may augment diastolic filling and minimize IDH. As outlined in a recent review of this topic, despite a paucity of prospective evidence on the optimal combinations and timing of antihypertensive medications in patients on hemodialysis, individualized adjustment in an attempt to minimize IDH may be considered for select patients (27).…”
Section: Maintenance Of Cardiac Outputmentioning
confidence: 99%
“…43 Most but not all reports have linked glucose absorption with the development of insulin resistance in nondiabetic patients on PD, 32,44,45 driven by higher levels of insulin, fasting plasma glucose, and triglycerides. 46 Additionally, a multicenter, open-label randomized study showed that lowering the glucose content of an automated PD regime resulted in lower insulin resistance at 90 days. 47 Insulin resistance is also associated with higher rates of cardiovascular disease.…”
Section: Pd-specific Factorsmentioning
confidence: 99%